1988
DOI: 10.1016/0014-5793(88)80109-1
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant interleukin‐1α‐mediated stimulation of procollagenase production and suppression of biosynthesis of tissue inhibitor of metalloproteinases in rabbit uterine cervical fibroblasts

Abstract: Influence of human recombinant interleukin‐1 (hrIL‐1) on collagen metabolism was investigated with rabbit uterine cervical fibroblasts. Enzyme‐linked immunosorbent assays for collagenase and tissue inhibitor of metalloproteinases (TIMP) indicated that hrIL‐1 participates in both stimulation of procollagenase production and suppression of TIMP synthesis by uterine cervical cells. IL‐1 did not modulate collagen synthesis. In addition, the sensitivity to IL‐1 of uterine cervix from ovariectomized rabbits was augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Interestingly, IL-6 has also been shown to enhance the synthesis of TGF-␤ (50), which might reinforce these feedback circuits. The contradictory results, which have shown that IL-1, depending on the conditions, can either stimulate or inhibit the synthesis of TIMP (17,19), suggest interactions and indirect effects through other cytokine receptors systems, including IL-6/IL-6R␣/sIL-6R␣.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, IL-6 has also been shown to enhance the synthesis of TGF-␤ (50), which might reinforce these feedback circuits. The contradictory results, which have shown that IL-1, depending on the conditions, can either stimulate or inhibit the synthesis of TIMP (17,19), suggest interactions and indirect effects through other cytokine receptors systems, including IL-6/IL-6R␣/sIL-6R␣.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, catabolic cytokines such as interleukin-1 (IL-1) and tumor necrosis factor-␣ (TNF-␣), the main promoters of MMPs synthesis and matrix degradation, have a marked inhibitory effect on TIMP-1 expression by chondrocytes, although some results have shown that IL-1, depending on the conditions, can either stimulate or inhibit the synthesis of TIMP-1 (15)(16)(17)(18)(19). IL-6 was initially considered a pro-inflammatory cytokine like TNF-␣ and IL-1, because of its IL-1-like effects on immune and hepatic cells.…”
mentioning
confidence: 99%
“…This process of apoptosis in ripening cervices resembles the deletion of cell popula tions that occurs in normal development and metamor phosis [28,29]. Furthermore, apoptosis is regulated by hormones [10,11,13,14], paracrines and cytokines [24][25][26][27], Interestingly, the onset of labor and cervical ripening has been shown to be regulated by estradiol and progester one antagonists [30][31][32][33], adrenocorticotropin [34] and prostaglandins [35].…”
Section: Discussionmentioning
confidence: 99%
“…Upon the death of cervical cells and subsequent infiltration of monocytes, proteolytic enzymes are re leased from these cells [24][25][26][27] that further degrade inter cellular materials including myosin and actin. These pro teases which modify the specific protease inhibitors may initiate the hydrolysis of connective tissues and lead to the softening of the cervix [24][25][26][27],…”
Section: Discussionmentioning
confidence: 99%
“…These interleukins are primarily recognized for their capacity to regulate innate and cognate immune responses, and are produced by a variety of cells participating in host defense against noxious agents [Dinarello, 1994b]. IL-1 has also been shown to regulate connective tissue metabolism, in particular by promoting degradation of ECM [Ito et al, 1988;Qwarnstrom et al, 1989]. Monocytes and macrophages are the principal source of IL-1 but resident cells such as keratinocytes, fibroblasts and endothelial cells can also produce IL-1 [Dinarello, 1994a].…”
mentioning
confidence: 99%